2002
DOI: 10.1080/02656730210129736
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock induces centrosomal dysfunction, and causes non-apoptotic mitotic catastrophe in human tumour cells

Abstract: Normal human diploid cells and various human tumour cells were heat shocked at 43 degrees C for 2h and allowed to recover at 37 degrees C. It was found that heat shock treatment transiently disrupted the immunostaining of centrosomes, and no centrosome staining was detected in either normal or tumour cells 24h after heat shock. Staining recovered thereafter in normal cells, but in tumour cells abnormal centrosomes, multiple and minute centrosomes were induced. While normal cells were arrested in G1 and G2 afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 32 publications
4
36
0
Order By: Relevance
“…Heat shock-mediated denaturation of key proteins in critical pathways affects many cellular functions. We surveyed several pathways known to be affected by heat shock and irradiation (23)(24)(25)(26)(27)(28)(29). Loss of mitochondrial membrane potential (Dw m ), an important initiator of cell death signaling (30,31), can be a consequence of heat shocks capable of denaturing protein and activating Hsf1 (23).…”
Section: Resultsmentioning
confidence: 99%
“…Heat shock-mediated denaturation of key proteins in critical pathways affects many cellular functions. We surveyed several pathways known to be affected by heat shock and irradiation (23)(24)(25)(26)(27)(28)(29). Loss of mitochondrial membrane potential (Dw m ), an important initiator of cell death signaling (30,31), can be a consequence of heat shocks capable of denaturing protein and activating Hsf1 (23).…”
Section: Resultsmentioning
confidence: 99%
“…HeLa nor K-562 cells increased expression of genes characteristically expressed in the G2/M phases of the cell cycle genes after 10 h of heat shock, suggesting a G2/M cell cycle arrest ( Figure 4D). It was previously reported that heat shock causes a transient G2/M arrest in primary cell lines, but not in many cancer cell lines (Nakahata et al, 2002).…”
Section: Heat Shockmentioning
confidence: 99%
“…It is well known that the onset of nuclear fragmentation is a hallmark of mitotic catastrophe (36). Mitotic catastrophe is distinguishable from apoptosis because it lacks DNA degradation that can be observed by either DNA laddering on agarose gel or TUNEL staining (37). To test whether increased mitotic catastrophe is the cause of increased toxicity in M2 cells, cells displaying nuclear fragmentation were scored at various time points after irradiation.…”
Section: Filamin-a and G 2 Arrestmentioning
confidence: 99%